Enzymatic Saccharification and Ethanol Fermentation of Reed Pretreated with Liquid Hot Water. (14th October 2012) - Lu, Jie; Li, XueZhi; Zhao, Jian; Qu, Yinbo
Abstract : Reed is a widespread-growing, inexpensive, and readily available lignocellulosic material source in northeast China. The objective of this study is to evaluate the liquid hot water (LHW) pretreatment efficiency of reed based on the enzymatic digestibility and ethanol fermentability of water-insoluble solids (WISs) from reed after the LHW pretreatment. Several variables in the LHW pretreatment and enzymatic hydrolysis process were optimized. The conversion of glucan to glucose and glucose concentrations are considered as response variables in different conditions. The optimum conditions for the LHW pretreatment of reed area temperature of 180°C for 20min and a solid-to-liquid ratio of 1 : 10. These optimum conditions for the LHW pretreatment of reed resulted in a cellulose conversion rate of 82.59% in the subsequent enzymatic hydrolysis at 50°C for 72 h with a cellulase loading of 30 filter paper unit per gram of oven-dried WIS. Increasing the pretreatment temperature resulted in a higher enzymatic digestibility of the WIS from reed. Separate hydrolysis and fermentation of WIS showed that the conversion of glucan to ethanol reached 99.5% of the theoretical yield. The LHW pretreatment of reed is a suitable method to acquire a high recovery of fermentable sugars and high ethanol conversion yield.